Investigation of the relationship between posterior semicircular canal benign paroxysmal positional vertigo and sleep quality (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the relationship between posterior semicircular canal benign paroxysmal positional vertigo (P-BPPV) and sleep quality.Material and Methods: In this prospective study, 35 patients with P-BPPV and 30 healthy volunteers were evaluated. Pittsburgh Sleep Quality Index (PSQI) and Insomnia Severity Index (ISI) were applied to all subjects. Adult Dizziness Handicap Index (ADHI) was applied to the patients with P-BPPV. The PSQI and ISI scores of the P-BPPV patient group and the control group were compared. ADHI scores were compared with PSQI and ISI scores. PSQI and ISI scores of recurrent P-BPPV patients and P-BPPV patients who had their first attack were compared.Results: The PSQI and ISI scores of the patients with P-BPPV were significantly worse than the control group (p=0.02, p0.001, respectively). There was no significant relationship between ADHI scores and PSQI and ISI scores in patients with P-BPPV (p=0.552, p=0.074, respectively). There was no significant difference between the PSQI and ISI scores of patients with recurrent P-BPPV and patients with non-recurrent P-BPPV (p=0.060, p=0.065, respectively). There was no significant difference between PSQI and ISI scores of P-BPPV patients who stated that sleep quality was negatively affected after vertigo attack and P-BPPV patients who stated that sleep quality was not affected after vertigo attack (p=0.405, p=0.919, respectively). Conclusion: Sleep quality of P-BPPV patients was significantly worse than the healthy volunteers. However, there was no relationship between the degree of disability due to imbalance after a vertigo attack and sleep quality in these patients. Poor sleep quality may cause P-BPPV. Improving sleep quality may reduce the rate of P-BPPV or reduce recurrence rates in P-BPPV patients.
Keywords: Benign paroxysmal positional vertigo; insomnia severity index; pittsburgh sleep quality index; sleep quality; vestibular.